Evaluating small conditional cash transfers to improve vaccine coverage and timeliness in Pakistan. (30th September 2020) - Abdullah, S; Siddiqi, D A; Shah, M T; Glennerster, R; Khan, A J; Chandir, S
Abstract: Background: Low immunization coverage rates have prompted the need to design effective demand-side interventions to improve uptake. Simple SMS reminders and large (≥USD 100) incentives have been demonstrated to effectively increase immunization coverage. However, research on small incentives (≤USD 15) for immunization is sparse and there is uncertainty regarding the optimal structure of incentives in terms of size, schedule, and design. Methods: A 12-arm randomized controlled trial is being conducted in Karachi, Pakistan with 10 incentive arms of varying size (amount), schedules (progressivity) and design (certainty of payment), an exclusive SMS arm and control arm. The incentives are provided through two mechanisms: mobile air time and mobile-money through a mobile-money provider. Children were enrolled when they presented to the study sites for either BCG, Penta-1, or Penta-2 vaccine. Results: A total of 11, 197 children were enrolled between Nov 2017 and Oct 2018 with approximately 800 children in each incentive arm and 1600 and 1599 in SMS and Control arm, respectively. As of Jan 09, 2020, Penta-3 and Measles-1 coverage are lowest in the control arm (71% and 60% respectively) and highest in the high-flat-lottery arm (78% and 69% respectively) with uniformly progressing incentive amounts along the immunization schedule. Discussion: Interim results suggest that small mobile-based incentives coupled with SMS reminders can significantly improve immunization coverage in children. The final analysis will provide robust evidence of this impact and provide policy implications for the most optimal incentive structure that can build caregiver demand for effectively increasing child immunization in an LMIC setting. Key messages: Small incentives (USD<15) coupled with simple SMS reminders can improve immunization coverage and timeliness in low resource settings in an inexpensive, logistically simple way. The study will provide experimental evidence on optimal incentive design, structure, and size of small incentives for a cost-effective approach to increase immunization coverage and timeliness.